(untitled) (Global Journal of Human-Social Science, 2024)
The article demonstrates how thinking works according to German philosopher G W F Hegel and shows what can go wrong if the reality Hegel relied on is compromised by images we encounter in the global world of media images a critique made by French philosopher Jean Baudrillard While people may connect with images on their devices rather than on television Baudrillard s analysis of images also applies to digital content This article examines the human task of learning to think for oneself in the company of other people Its central question focuses on the path thoughtfulness takes if thinking is authentically personal and socially sound The article offers a model for thinking abduction that allows us to keep in touch with reality as we learn to think together about our opinions knowledge and beliefs The article suggests a hopeful way forward for learning to think based on Western philosopher Immanuel Kant s approach to thegrowth of the intellect